Impaired Right, Left, or Biventricular Function and Resting Oxygen Saturation Are Associated With Mortality in Eisenmenger Syndrome: A Clinical and Cardiovascular Magnetic Resonance Study. (December 2015) - Jensen, Annette S.; Broberg, Craig S.; Rydman, Riikka; Diller, Gerhard-Paul; Li, Wei; Dimopoulos, Konstantinos; Wort, Stephen J.; Pennell, Dudley J.; Gatzoulis, Michael A,; Babu-Narayan, Sonya V.
Abstract : Background—: Patients with Eisenmenger syndrome (ES) have better survival, despite similar pulmonary vascular pathology, compared with other patients with pulmonary arterial hypertension. Cardiovascular magnetic resonance (CMR) is useful for risk stratification in idiopathic pulmonary arterial hypertension, whereas it has not been evaluated in ES. We studied CMR together with other noninvasive measurements in ES to evaluate its potential role as a noninvasive risk stratification test. Methods and Results—: Between 2003 and 2005, 48 patients with ES, all with a post-tricuspid shunt, were enrolled in a prospective, longitudinal, single-center study. All patients underwent a standardized baseline assessment with CMR, blood test, echocardiography, and 6-minute walk test and were followed up for mortality until the end of December 2013. Twelve patients (25%) died during follow-up, mostly from heart failure (50%). Impaired ventricular function (right or left ventricular ejection fraction) was associated with increased risk of mortality (lowest quartile: right ventricular ejection fraction, <40%; hazard ratio, 4.4 [95% confidence interval, 1.4–13.5]; P =0.01 and left ventricular ejection fraction, <50%; hazard ratio, 6.6 [95% confidence interval, 2.1–20.8]; P =0.001). Biventricular impairment (lowest quartile left ventricular ejection fraction, <50% and right ventricular ejection fraction, <40%) conveyed an even higher risk of mortality (hazard ratio, 8.0 [95% confidence interval, 2.5–25.1]; P =0.0004). No other CMR or noninvasive measurement besides resting oxygen saturation (hazard ratio, 0.90 [0.83–0.97]/%; P =0.007) was associated with mortality. Conclusions—: Impaired right, left, or biventricular systolic function derived from baseline CMR and resting oxygen saturation are associated with mortality in adult patients with ES. CMR is a useful noninvasive tool, which may be incorporated in the risk stratification assessment of ES during lifelong follow-up.